Indo-cyanine green administration to identify loss of lymph after axillary lymph node dissection - Roman, Mirela Mariana; Delrue, Pauline; Karler, Clarence; Del Marmol, Véronique; Bourgeois, Pierre (Frontiers in Oncology, 2023)
Background. Near Infra-red fluorescence imaging with Indocyanine Green (ICG) is now used for the imaging of lymph nodes and lymphatic vessels. In this work, we investigated the impact of its pre-operative and per-operative administration on our ability to detect axillary lymphatic loss after breast cancer surgery. Methods. One subcutaneous injection of ICG was administered in the ipsilateral hand of 109 women who were scheduled to have either a mastectomy with total axillary lymph node dissection (CALND) or a lumpectomy with selective lymphadenectomy (SLN) the day before (n = 53) or the same day of surgery (n = 56). The lymph leakages were assessed by means of the application of a compress in the operated armpit and by the presence or not of fluorescence on it as well as in the post-operative axillary drains. Results. The compress was fluorescent in 28% of SLN patients and 71% of CALND patients. The liquids in the axillary drains were also fluorescent in 71% of the patients with CALND. No statistical significance was observed between the ICG injection groups. The association between a compress fluorescent and the presence of fluorescence in the axillary drains is significant in the pre-operative subgroup and in the whole group. Conclusion: Our research demonstrates that lymphatic leaks aid in the development of seromas and calls into question the effectiveness of the ligatures and/or cauterizations used during surgery. A prospective, multicentric, randomized trial should be conducted to verify the efficacy of this approach.